2014
DOI: 10.1111/bcpt.12360
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Flavonoids Added to Pharmacological Antihypertensive Therapy are Effective in Improving Blood Pressure

Abstract: Epidemiological studies have suggested that the daily intake of flavonoids is associated with a decreased risk of developing cardiovascular disease. Our purpose was to evaluate the effect of the addition of dietary flavonoids (DF) to antihypertensive treatment (AHT), based on telmisartan (Tms) or captopril (Cpr), on blood pressure (BP), body mass index (BMI), waist/hip ratio, leptin, lipid profile and inflammation in hypertensive young patients. An open-label, randomized, controlled trial was performed among 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Titles and abstracts of 813 articles were read, and 774 articles were excluded. By considering criteria for inclusion and exclusion, 22 articles were excluded due to following reasons: not having a control group ( N = 3; Alghadir, Gabr, & Al‐Eisa, ; Lee et al, ; Sung et al, ), intervention less than 1 day ( N = 3; Alexopoulos et al, ; Hsu et al, ; Koutelidakis et al, ), and using other nutrients beside green tea in the intervention group ( N = 16; Bakker et al, ; Braga et al, ; Cialdella‐Kam et al, ; de Jesus Romero‐Prado et al, ; Dominiak, McKinney, Heilbrun, & Sarkar, ; Kim et al, ; Madaric et al, ; Nieman et al, ; Nieman et al, ; Ormsbee et al, ; Peluso et al, ; Rondanelli et al, ; Rubio‐Perez, Albaladejo, Zafrilla, Vidal‐Guevara, & Morillas‐Ruiz, ; Scolaro et al, ; Soriano‐Maldonado, Hidalgo, Arteaga, de Pascual‐Teresa, & Nova, ; Thomas, Williams, Sharma, Chaudry, & Bellamy, ; Figure ). Therefore, 17 articles were included in our systematic review (Basu et al, ; Bogdanski et al, ; de Maat et al, ; Dower et al, ; Fukino et al, ; Fukino, Shimbo, Aoki, Okubo, & Iso, ; Gutierrez‐Salmean et al, ; Hu et al, ; Hussain, Habib Ur, & Akhtar, ; Mielgo‐Ayuso et al, ; Mombaini & Jafarirad, ; Nogueira, Nogueira Neto, Klein, & Sanjuliani, ; Oyama et al, ; Oyama, Maeda, Sasaki, et al, ; Ryu et al, ; Shin et al, ; Sone et al, ); because the article by Ryu et al () did not report baseline values, we did not include it in our meta‐analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Titles and abstracts of 813 articles were read, and 774 articles were excluded. By considering criteria for inclusion and exclusion, 22 articles were excluded due to following reasons: not having a control group ( N = 3; Alghadir, Gabr, & Al‐Eisa, ; Lee et al, ; Sung et al, ), intervention less than 1 day ( N = 3; Alexopoulos et al, ; Hsu et al, ; Koutelidakis et al, ), and using other nutrients beside green tea in the intervention group ( N = 16; Bakker et al, ; Braga et al, ; Cialdella‐Kam et al, ; de Jesus Romero‐Prado et al, ; Dominiak, McKinney, Heilbrun, & Sarkar, ; Kim et al, ; Madaric et al, ; Nieman et al, ; Nieman et al, ; Ormsbee et al, ; Peluso et al, ; Rondanelli et al, ; Rubio‐Perez, Albaladejo, Zafrilla, Vidal‐Guevara, & Morillas‐Ruiz, ; Scolaro et al, ; Soriano‐Maldonado, Hidalgo, Arteaga, de Pascual‐Teresa, & Nova, ; Thomas, Williams, Sharma, Chaudry, & Bellamy, ; Figure ). Therefore, 17 articles were included in our systematic review (Basu et al, ; Bogdanski et al, ; de Maat et al, ; Dower et al, ; Fukino et al, ; Fukino, Shimbo, Aoki, Okubo, & Iso, ; Gutierrez‐Salmean et al, ; Hu et al, ; Hussain, Habib Ur, & Akhtar, ; Mielgo‐Ayuso et al, ; Mombaini & Jafarirad, ; Nogueira, Nogueira Neto, Klein, & Sanjuliani, ; Oyama et al, ; Oyama, Maeda, Sasaki, et al, ; Ryu et al, ; Shin et al, ; Sone et al, ); because the article by Ryu et al () did not report baseline values, we did not include it in our meta‐analysis (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…not having a control group (N = 3;Alghadir, Gabr, & Al-Eisa, 2016;Lee et al, 2005;Sung et al, 2005), intervention less than 1 day (N = 3;Alexopoulos et al, 2008;Hsu et al, 2007;Koutelidakis et al, 2014), and using other nutrients beside green tea in the intervention group (N = 16;Bakker et al, 2010;Braga et al, 2012;Cialdella-Kam et al, 2016;de Jesus Romero-Prado et al, 2015;Dominiak, McKinney, Heilbrun, & Sarkar, 2010;Kim et al, 2016;Madaric et al, 2013;Nieman et al, 2013;Nieman et al, 2017;Ormsbee et al, 2014;Peluso et al, 2014;Rondanelli et al, 2013;Rubio-Perez, Albaladejo, Zafrilla, Vidal-Guevara, & Morillas-Ruiz, 2016; Scolaro et al, 2018; Soriano-Maldonado, Hidalgo, Arteaga, de Pascual-Teresa, & Nova, 2014; Thomas, Williams, Sharma, Chaudry, & Bellamy, 2014; Figure 1).Therefore, 17 articles were included in our systematic review(Basu et al, 2011;Bogdanski et al, 2012;de Maat et al, 2000;Dower et al, 2015;Fukino et al, 2008;Fukino, Shimbo, Aoki, Okubo, & Iso, 2005;Gutierrez-Salmean et al, 2016;Hu et al, 2016;Hussain, Habib Ur, & Akhtar, 2017;Mielgo-Ayuso et al, 2014;Mombaini & Jafarirad, 2017;Nogueira, Nogueira Neto, Klein, & Sanjuliani, 2017;Oyama, Maeda, Sasaki, et al, 2010;Ryu et al, 2006;Shin et al, 2018;Sone et al, 2011)…”
mentioning
confidence: 99%
“…After detailed analysis of the full text, 71 articles were excluded, due to lack of relevant outcomes, aspects of study design or publication language. The final number of articles selected for meta-analysis was selected from a total of 117 articles published between 1997 and July 2015 (included) [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have suggested that the daily intake of flavonoids is associated with a decreased risk of developing cardiovascular disease [57].…”
Section: Flavonoidsmentioning
confidence: 99%